1994
DOI: 10.1300/j077v12n03_04
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Breast Cancer from the Perspectives of Husbands and Wives

Abstract: In a cross-sectional study, 36 breast cancer patients and Iheir husbands provided information about how each recalled coping with stress during a course of radiation Iherapy. Both spouses also were askcd lo repon on onc anou~er's coping efforts and to provide information about Lheir own current psychological adjustment and marital satisfaction. The results indicated that wives engaged in more extensive and varicd coping cflorts than their husbands did and h a t the coping strategies which husbands and wives us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 32 publications
1
74
1
Order By: Relevance
“…Examples of items that participants endorsed included "avoid being with people in general," "refuse to believe it will happen," and "wish the situation would go away." This type of coping has been associated with poorer outcome in the cancer literature [36], specifically when examining husbands of patients [21,37].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of items that participants endorsed included "avoid being with people in general," "refuse to believe it will happen," and "wish the situation would go away." This type of coping has been associated with poorer outcome in the cancer literature [36], specifically when examining husbands of patients [21,37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research with patients with other types of cancer similarly has found poorer adjustment among patients using avoidant coping strategies. [6][7][8][9][10][11]28 On balance, evidence from divergent samples suggests that coping through avoidance is maladaptive in response to a chronic stressor such as cancer. 29 Conclusions concerning emotion-focused coping are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Coping refers to cognitive and behavioral efforts to manage situations that are perceived as stressful. 5 Among patients with various types of malignancies, coping has been significantly associated with distress, [6][7][8][9][10][11][12] health-related quality of life, 13,14 and in some studies, immune activity 15 and survival. 16,17 In a number of investigations coping is a more robust predictor of quality of life outcomes than medical variables such as extent of disease or type of treatment.…”
mentioning
confidence: 99%
“…By virtue of their social roles, patients and partners may have very different perspectives on the cancer experience [12,37,38]. Talking provides an opportunity for spouses to fuse two independent perspectives into a connected sense of meaning [39,40].…”
Section: Introductionmentioning
confidence: 99%